Indigenous Voices | AfroDiasporic & Indigenous Studies Collection - Williamson, Tara; Coulthard, Glen; Gordan, Jessica; Wilson, Nina; McAdam, Syliva; McLean, Sheelah; Horn-Miller, Waneek (Advancing Nonviolence and Social Transformation New Perspectives on Nonviolent Theories, 2016)
Nonviolence is emerging as a topic of great interest in activist, academic and community settings. In particular, nonviolence is being recognized as a necessary component of constructive and sustainable social change. This book considers nonviolence in relationship to specific social, political, ecological and spiritual issues. Through case studies and examinations of social resistance, gender, the arts, and education, it provides specialists and non-specialists with a solid introduction to the importance and relevance of nonviolence in various contexts.Advancing Nonviolence and Social Transformation is organized into five sections. The first section is a set of essays on various historical and contemporary perspectives on nonviolence. The second section consists of essays on philosophical and theoretical explorations of the topic. The third and fourth sections expand the scope of nonviolence into the areas of thought and action, including Indigenous resistance, student protests, human trafficking, intimate partner violence and ecological issues. The final section takes nonviolence into the study of wonder, music, education and hope. The book will be useful to anyone working in the theories and practices of social change.
Keywords: Sylvia Mcadam